DETERMINATION OF UNKNOWN RESISTANCE USING UITSON BRIDGE (ResearchJet Journal of Analysis and Inventions, 2023)
In nature, there is a force that resists every force and it manifests itself in different forms. For example, there is a resistance force of the air acting on an object going up or down, whether it is horizontal or vertical, there is also a thermal resistance that prevents the thermal motion of the molecules of the objects from spreading, a part of the circuit is connected to the electric current There is also electrical resistance, a physical quantity that represents the feedback effect.[1] The purpose of this laboratory work is to determine the unknown electrical resistance using the Wheatstone bridge and to verify that the measurement of the unknown resistance does not depend on the current flowing through the resistance in the zero balance method. In 1833, Samuel Hunter Christie presented his "diamond" method, i.e., the Wheatstone bridge, in the form of the electrical properties of metals, as a method of comparing the resistance of wires of different thicknesses at the Royal Society's Baker Lecture.[2] However, this method was not recognized until 1843. Charles Wheatstone proposed it in another paper for the Royal Society to measure resistance in electrical circuits. Although Wheatstone introduced it as an invention of Samuel Hunter Christie, it is now associated with the method.